A Analysis Of Economic Business Sangkuriang Catfish (Clarias gariepinus) Hatchery At CV. Sumber Rezeki in Padang Pengrapat Village, Tanah Grogot Subdistrict, Paser Regency: Analisis Ekonomi Usaha Pembenihan Ikan Lele Sangkuriang (Clarias gariepinus) di CV. Sumber Rezeki Desa Padang Penhrapat Kecamatan Tanah Grogot Kabupaten Paser - Robi Robi; Fitriyana; Bambang Indratno Gunawan (2339-1324, 2024)
The purpose of this research was to know the stages of sangkuriang catfish hatchery and to calculate performance of economic business sangkuriang catfish hatchery based on a eligibility analysis which cover; Revenue Cost Ratio (RCR), Price Point Break Event, Sales Point Break Event, Production Point Break Event, Payback Period, and Return On Investment. This research was conducted from July 2021 to February 2022. The type of research data using quantitative data and primary data obtained by interview using questionnaires. The research showed that value of RCR = 4.25, break even point of price in amount of Rp. 101/tail < actual price in amount of Rp. 450/tail, break even point of sales in amount of Rp. 694,705/month < actual sales in amount Rp. 39,000,000/month, break even point of quantity in amount of 1,951 tail/month < quantity in amount of 90,000 tail/month, payback period for 11 months 24 days, and results of ROI analysis obtained amount 93.25%. The results analysis performance of economic indicate that business of sangkuriang catfish hatchery business in CV. Sumber Rezeki profitable and feasible to do.